Efficiency of Commercial Banking in Developing Countries - Cvetkoska, Violeta; Fotova Cikovic, Katerina; Tasheva, Marija (MDPI, 2021)
The aim of this paper is to evaluate the relative efficiency of commercial banks in three developing countries in Europe (North Macedonia, Serbia, and Croatia) in the period from 2015 to 2019, and to provide targets for improvement for the inefficient banks by using DEA. The variables are selected under the income-based approach. Based on the output-oriented BCC model, unusual results are obtained for a few commercial banks in each country, that is, they are BCC relative efficient, which is contrary to the real situation. In order to identify outliers that can affect the efficiency results, a super-efficiency procedure is applied so that banks with a super-efficiency score higher than 1.2 (outliers) or for which a feasible solution was not found are considered in detail and removed, and then the output-oriented BCC model is rerun. Based on the obtained results, the Macedonian commercial banking system shows the highest efficiency (91.1%), followed by the Croatian (90.9%) and the Serbian (81.9%) banking system. The estimated targets for improvement of the inefficient commercial banks could help their top bank management in better resource allocation and making fact-based and faster decisions by which they can improve the operation of the banks they lead and contribute to the stability of the financial system.
Keywords: bank efficiency; developing countries; Data Envelopment Analysis; BCC; super-efficiency; targets for improvement